FRI0529 Comparative risks for serious infections associated with biologics in high risk rheumatoid arthritis patients. (23rd January 2014) - Yun, H.; Xie, F.; Delzell, E.; Chen, L.; Levitan, E.; Lewis, J.; Saag, K. G.; Beukelman, T.; Winthrop, K. L.; Baddley, J. W.; Muntner, P.; Curtis, J. R.
Abstract : Background: Serious infections are an important concern for patients with rheumatoid arthritis (RA) treated with biologic agents. However, insufficient data guide the optimal treatment in the high risk population. Objectives: To compare the subsequent risk of hospitalized infections associated with specific biologic agents among RA patients previously hospitalized for infection while receiving anti-TNF therapy. Methods: Using Medicare data from 2006-2010 for 100% of beneficiaries with RA, we identified patients who were hospitalized with infection while on anti-TNF agents and who had US Medicare fee-for-service hospital, physician and prescription drug coverage continuously in the 6 months before the hospitalization discharge date and throughout follow up. Follow-up began 60 days after hospital discharge and ended at the time of next infection, loss of Medicare coverage or after 18 months. We determined biologic exposure on each person-day during follow-up and treated exposure as time varying. Confounding was controlled through a person-specific infection risk score that was separately derived among new users of anti-TNF and non-biologic DMARDs. We calculated the subsequent incidence rate of hospitalized infection for each biologic and used cluster adjusted Cox regression to evaluate the association between various biologics and subsequent infection, controlling for infection risk score decile. Results: During follow-up of 13, 076 hospitalized infections while exposed to anti-TNF therapy, we identified 13, 772 person-years of exposure to biologics; of this time 5% was on abatacept, 2% on rituximab and 93% on anti-TNFs, including 23% on etanercept, 18% on adalimumab and 52% on infliximab. Abatacept users had the lowest crude incidence rate of subsequent hospitalized infection, and etanercept users had the highest. After adjusting for infection risk score decile and the original anti-TNF medication, abatacept (hazard ratio (HR): 0.80, 95% CI: 0.68-0.95) and etanercept (HR: 0.84, 95% CI: 0.74-0.96) users had significantly lower risks of infection compared to infliximab users. (Table ) Image/graph: Conclusions: Among Rheumatoid Arthritis patients at high risk for recurrent serious infection who experienced a hospitalized infection while on anti-TNF therapy, abatacept and etanercept appear to be associated with the lowest risk of subsequent infection among the commonly prescribed biologic therapies. Acknowledgements: This work was supported by (R01 HS018517). Dr. Curtis receives support from the NIH (AR 053551) Disclosure of Interest: H. Yun: None Declared, F. Xie: None Declared, E. Delzell Grant/research support from: Amgen, L. Chen: None Declared, E. Levitan: None Declared, J. Lewis Grant/research support from: Shire, Takeda and Centocor, Consultant for: Amgen, Millennium Pharmaceuticals, Pfizer, Abbott, Prometheus, Nestle, Lilly and Shire, K. Saag Grant/research support from: ACAR, Ardea, Savient, Takeda, Regeneron, Consultant for: Ardea, Regeneron, Takeda, Savient, T. Beukelman Grant/research support from: Pfizer, Consultant for: Novartis, Genentech, Roche, K. Winthrop Grant/research support from: Pfizer, Consultant for: UCB, Pfizer, Genentech, J. Baddley Consultant for: Pfizer, Astellas, Merck, Mayne Pharma, P. Muntner: None Declared, J. Curtis Grant/research support from: Roche/Genentech, UCB, Janssen, CORRONA, Amgen, Pfizer, BMS, Crescendo, AbbVie, Consultant for: Roche/Genentech, UCB, Janssen, CORRONA, Amgen, Pfizer, BMS, Crescendo, AbbVie